Association between fatigue and MDS-UPDRS in individuals with Parkinson’s disease: cross-sectional study - Terra, Marcelle Brandão; Lopes, Josiane; Bueno, Maria Eduarda Brandão; Trinca, Luzia Aparecida [UNESP]; Smaili, Suhaila Mahmoud (Springer Nature, 2024)
Background: Fatigue is significant in the context of Parkinson’s disease (PD), considering that one-third of patients classify it as the most restricting symptom in their daily life activities (DLAs). The objective was to verify the relationship (association) between fatigue and non-motor and motor symptoms of PD. Methods: A cross-sectional study which included 100 individuals with PD. Initially, demographic and clinical data (modified Hoehn and Yahr scale—HY, anxiety, and depression) were collected. To assess the non-motor and motor symptoms of PD, the Movement Disorders Society—Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) was applied. Fatigue was evaluated using the Parkinson Fatigue Scale. Results: A higher HY score, greater severity of non-motor aspects of DLAs and motor aspects of DLAs, more motor complications, and higher levels of anxiety as well as depression were observed in the fatigue group. Fatigue was associated with a lower daily equivalent levodopa dose (LEDD), a higher body mass index (BMI), anxiety, depression, and the presence of non-motor symptoms. Conclusion: Non-motor symptoms are more determining factors for fatigue than the motor condition itself, with an association between fatigue and higher BMI scores, increased anxiety and depression, lower LEDD, and greater severity of non-motor aspects of DLAs. Individuals in the fatigue group had higher HY scores, anxiety, and depression, worse non-motor and motor symptoms related to experiences of daily life, as well as motor complications.
Keywords: Fatigue; Non-motor symptoms; Parkinson’s disease; Signs and Symptoms